Scrub Typhus in Western Nepal: A Series of Case Reports - Prajwal Pudasaini; Annu Ranjit; Saraswoti Neupane (Nepal Journal of Dermatology, Venereology & Leprology)
Scrub typhus, a mite borne infectious disease which is transmitted to humans by bite of trombiculid mite. An eschar, which is a characteristic necrotic skin lesion, is formed at the site of bite. Systemic spread via the hematogenous and lymphatic routes occur and the infected people develop fever, cutaneous rash, myalgia, and lymphadenopathy. Diagnosis of scrub typhus is often difficult because of vast variability and non-specific presentation of the disease. Scrub typhus has been poorly reported from Kaski district. Here we report series of five cases of scrub typhus from Kaski distrist of Western Nepal.